Depression, anxiety, stress symptoms and their determinants among secondary students with vision impairment in rural Northwestern China during the COVID-19 pandemic - Li, Dongfeng; Chan, Ving Fai; Wang, Huan; Zhang, Huiping; Virgili, Gianni; Whitestone, Noelle; Xiao, Baixiang; Singh, Manpreet K.; She, Xinshu; Mackenzie, Graeme; Boswell, Matthew; Mavi, Sonia; et al. (Frontiers in Public Health, 2024)
Objective: The measures implemented to control the spread of Coronavirus disease 2019 (COVID-19) could affect children's mental and vision health. Youth particularly from minority and socioeconomically disadvantaged backgrounds were more likely to be impacted by these measures. This study aimed to examine the mental health of children with vision impairment and associated factors in North-western China during the COVID-19 pandemic. Methods: A cross-sectional study was conducted among 2,036 secondary school children living in Ningxia Hui Autonomous Region. Participants completed a survey on sociodemographic and lifestyle information and answered the Chinese version of the 21-item Depression Anxiety Stress Scales (DASS-21) questionnaire. Presenting visual acuity was measured by a trained enumerator. Multivariate logistic regressionanalysis was used to identify potential risk factors for mental health problems.Responses from 1,992 (97.8%) children were included in the analysis after excluding those with incomplete mental health outcome data. The prevalence of depression, anxiety and stress symptoms within the dataset were 28.9%, 46.4%, and 22.3%, respectively. The distribution of children with different stress levels differed significantly between those with and without vision impairment (p=0.03).Multivariable logistic regression analyses revealed that depression symptoms decreased with higher parental education (OR, 0.76, 95% confidence intervals (CI):0.63-0.96), longer sleep duration (OR, 0.90, 95% CI:0.81-0.97) and longer study time (OR, 0.82, 95% CI: 0.74-0.91), whereas they increased with higher recreational screen time (OR, 1.19, 95% CI:1.08-1.32). Anxiety symptoms decreased with higher parental education (OR, 0.80, 95% CI:0.66-0.96) and increased with higher recreational screen time (OR, 1.15, 95% CI:1.04-1.27) and being a left-behind child (OR, 1.26, 95% CI:1.04-1.54). In addition, stress symptoms decreased with longer sleep duration (OR, 0.92, 95%CI:0.85-0.99) and increased with higher number of siblings (OR, 1.10, 95% CI:1.01-1.19), higher recreational screen time (OR, 1.15, 95% CI:1.04-1.28) and older age (OR,1.12, 95% CI: 1.004-1.24).: A considerable proportion of our sample experienced mental health problems during the pandemic. Healthcare planners in China should consider interventions such as reducing recreational screen time, ensuring sufficient sleep, and timely detection of mental health symptoms among socioeconomically disadvantaged groups.